Correlation between the ninth grade students’ learning habitand reading comprehension junior high school - Sunan Hadi Putra (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The results of this research are expected to help the students to know themselves about their learning habits. Give information to the English teachers about students’ characteristics, especially about learning. So, they can anticipate it.And also to know the students’ ability in reading.This study is quantitative research with correlation research design. The correlation study is a study that involves collecting data in order to determine the degree to which a relationship exists between two or more variables. The result showed that the value of the coefficient correlation between Students’ Habits (X1) and Reading Comprehension (Y) for -0.011. Sig. Value 0.923 was higher than Alpha value 0.05 (0.923 >0,2213).